2018
DOI: 10.15386/cjmed-999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of calcium hydroxide and endodontic irrigants on the push-out bond strength of fiber post - an in vitro study

Abstract: BackgroundIn recent years, fibre-reinforced composite posts have been proposed for the restoration of root filled teeth as an alternative to pre-fabricated posts or metal dowels.Aims and objectivesThe aim of the study was to analyze the effect of endodontic irrigants used for removal of calcium hydroxide on the push-out bond strength of fiber posts to root canal dentin.MethodsForty human permanent single-rooted mandibular premolars with relatively straight roots were taken and access cavities were prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…They explained that this finding might be attributed to effective elimination of the smear layer by QMix (Gündoğar et al, 2018). Assessing the effect of different irrigating solutions, used for elimination of calcium hydroxide from the root canal system, on the bond strength of fiber‐reinforced composite posts revealed maximum bond strength in the QMix group, followed by MTAD and NaOCl/EDTA groups (Chaudhary et al, 2018). In 2013, Elnaghy et al evaluated the effect of QMix on bond strength of glass fiber posts to root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…They explained that this finding might be attributed to effective elimination of the smear layer by QMix (Gündoğar et al, 2018). Assessing the effect of different irrigating solutions, used for elimination of calcium hydroxide from the root canal system, on the bond strength of fiber‐reinforced composite posts revealed maximum bond strength in the QMix group, followed by MTAD and NaOCl/EDTA groups (Chaudhary et al, 2018). In 2013, Elnaghy et al evaluated the effect of QMix on bond strength of glass fiber posts to root dentin.…”
Section: Discussionmentioning
confidence: 99%
“…13 In fact, studies have shown that calcium hydroxide cannot be completely removed from root canals with any of a wide range of commonly used devices or techniques, [14][15][16][17] and it has been suggested that residual calcium hydroxide may reduce the bond strength of fiber posts subsequently applied to root canals. [18][19][20] Ceramics are inorganic, non-metallic materials formed by subjecting raw minerals to high temperatures. 21 Bioceramics refer to both biocompatible ceramic materials and metal oxides that possess good sealing, antibacterial and antifungal characteristics, and are used in medicine and dentistry 22 for their ability to mimic or induce tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition to intracanal medicaments that change the structure of rootcanal dentin, bonding at dentin-cement-post interfaces can also be affected by root-canal irrigation solutions, filling materials, and bioceramics as well as by the preparation of the post space and the presence/thickness of a smear layer. 20 Perforation repair materials and their interactions with residual calcium hydroxide used as an intercanal medicament may affect the bond strength of prefabricated fiber posts. This in vitro study compared the effects of four different root-repair materials (MTA, Biodentine, BioAggregate, EndoSequence BC) with and without calcium hydroxide on the bond strength of fiber posts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations